Nomenclatural notes and typification of names in Maranta (Marantaceae) - Fraga, Fernanda Ribeiro De Mello; Braga, João Marcelo Alvarenga (Phytotaxa, 2020)
In the present study we designate lectotypes for 19 names, as well as a neotype for Maranta phrynioides. Furthermore, an illustration is recognized as the holotype of M. bicolor, based on historical data, and the unknown type of M. noctiflora is here located and its history is clarified. Finally, important taxonomic notes are provided, including the new synonyms Calathea stenostachys, M. longipes, M. longiscapa, M. pleiostachys and M. pycnostachys, all under M. phrynioides, as well as M. subterranea as a synonym of M. furcata.